European Green Deal - Kazak, Tchetin (Yearbook of the Law Department, 2020)
This article aims to present the main objectives and characteristics of the European Green Deal, which is a kind of roadmap for achieving the sustainability of the EU economy by turning climate and environmental challenges into opportunities in all policy areas, through a just and inclusive transition for all. The implementation of this roadmap provides for actions to use resources efficiently by moving to a circular economy, reducing biodiversity loss and diminishing pollution. The roadmap also sets out the necessary investments and financial instruments and the need to ensure a just and inclusive transition. Transforming the economy of the European Union (EU) into a resource-efficient economy in which economic growth is not directly linked to the use of resources, based on the cessation of net emissions by 2050. The European Green Deal outlines a plan for this transformative change.